Improvement Of Science And Science Learning Outcomes For Elementary School Students In Grade Iii Ecosystem Materials By Using The Roleplaying Roleplaying Method - Bahari, Dyta Putri; Mursidik, Elly’s Mersina; Sujianti, Reni (Riviera Publishing, 2024)
Low learning outcomes of grade III students of SDN Sobrah in the subject of science and natural sciences on the material of ecosystem components. Based on initial observations, out of 20 students, only eight could achieve the KKM (Minimum et al.) of 75. This study aims to improve student learning outcomes using the Role Playing learning method. This study uses a Classroom Action Research (CAR) approach with qualitative and quantitative descriptive data analysis methods. Data collection techniques include observation, interviews, and tests. The study's results showed that the roleplaying method improves roleplaying student learning outcomes. The percentage of learning completion increased from 40% in the pre-cycle stage to 70% in cycle I and reached 85% in cycle II. This increase shows that Role-PlayingRoleplaying effectively provides meaningful learning experiences and encourages active student involvement. The implications of this study indicate that contextual and interactive learning methods, such as Roleplaying, can be an effective strategy for improving learning outcomes, especially in science and natural sciences subjects with complex materials.